Design & Fabrication of Instant Coconut Cutter - Ngadimon, Khairulnizam; Mohd Faizal Anuar, Muhammad Danish Zakwan; Roslan, Mohammad Faiz; Azizan, Mohamad Azfarhad (Multidisciplinary Applied Research and Innovation, 2025)
The project Instant Coconut Cutter reflects a novel approach to introduce an innovative way of making coconut opening easier, faster, safer and more convenient for domestic purposes as well as small scale commercial operations. In the past, coconuts opened manually with a knife/machete to remove the coconut flesh, but this demanded physical strength, skill and time as well as being dangerous. The Instant Coconut Cutter circumvents these concerns by incorporating a blade for cutting mechanism coupled with an ergonomic and portable design to provide uniform and accurate cutting without slipping. Aluminum based design water compartment, basin, stainless steel circular blade, and a strong clamping system are all employed by the device to ensure that when it slices into a coconut or through an exoskeleton, nothing slips freely. Supporting user-friendliness, portability and maintainability, the design can be used for domestic as well as professional purposes. Test results showed the device is capable of halving coconut shells in less than 20 s, accompanied by a 60% decrease in user effort when compared to manual slitting method. Not just that, many advantages include the fact the compartment is made of food grade stainless steel, hygiene compliance and toughness come as a standard. In summary, the Instant Coconut Cutter is an innovative device for processing coconuts which will save time and enhance safety features used and hence it offers plenty of practical leverage uniting traditional food preparation to a more modern design.